2016
DOI: 10.1038/bcj.2016.90
|View full text |Cite
|
Sign up to set email alerts
|

High levels of periostin correlate with increased fracture rate, diffuse MRI pattern, abnormal bone remodeling and advanced disease stage in patients with newly diagnosed symptomatic multiple myeloma

Abstract: Periostin is an extracellular matrix protein that is implicated in the biology of normal bone remodeling and in different cancer cell growth and metastasis. However, there is no information on the role of periostin in multiple myeloma (MM). Thus, we evaluated periostin in six myeloma cell lines in vitro; in the bone marrow plasma and serum of 105 newly diagnosed symptomatic MM (NDMM) patients and in the serum of 23 monoclonal gammopathy of undetermined significance (MGUS), 33 smoldering MM (SMM) patients, 30 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…34 High circulating periostin levels are correlated with reduced bone formation and increased bone resorption. 34 Although recent epidemiological studies indicate that decreased bone mineral density is associated with increased CVD burden, 35,36 the underlying mechanism linking increased POSTN expression with reduced calcification in coronary arteries warrants further investigation. 37,38 The 4 loci previously identified for CAC ( APOB at 2p24.1, 13 PHACTR1 at 6p24.1, 13,14 CDKN2B at 9p21.3, 13,14 and APOE at 19q13.32 13 ) were all associated with coronary artery disease risk, confirming increased CAC as a biomarker of coronary artery disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…34 High circulating periostin levels are correlated with reduced bone formation and increased bone resorption. 34 Although recent epidemiological studies indicate that decreased bone mineral density is associated with increased CVD burden, 35,36 the underlying mechanism linking increased POSTN expression with reduced calcification in coronary arteries warrants further investigation. 37,38 The 4 loci previously identified for CAC ( APOB at 2p24.1, 13 PHACTR1 at 6p24.1, 13,14 CDKN2B at 9p21.3, 13,14 and APOE at 19q13.32 13 ) were all associated with coronary artery disease risk, confirming increased CAC as a biomarker of coronary artery disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated circulating activin A levels have been associated with advanced MM features and adverse prognosis 44 . Increased activin A levels have also been correlated with elevated serum periostin in newly diagnosed MM patients 46 . It has been reported that the crosstalk between BMSCs and MM cells induces activin A secretion 45 .…”
Section: Molecular Pathways Primarily Implicated In Increased Osteoclmentioning
confidence: 99%
“…Both newly diagnosed and relapsed patients present with elevated levels of periostin in bone marrow plasma and in serum compared to SMM, MGUS, and healthy controls. High periostin levels are also associated with extensive bone lytic lesions, bone fractures and advanced disease characteristics 46 . Interestingly, monoclonal antibodies targeting periostin have emerged with promising results in preclinical models of breast and ovarian cancer 88 ; nevertheless, their role in MM pathogenesis remains to be investigated.…”
Section: Molecular Pathways Primarily Implicated In Suppressed Osteobmentioning
confidence: 99%
“…When sFRP-2 was immunosuppressed, an increase in OB matrix mineralisation was also seen, suggesting sFRP-2 as a potential target for MBD treatment [33], viz., that it is possible to block and reverse its effects. Periostin, a cell-adhesion protein, also inhibits Wnt pathways, with elevated levels in MM associated with osteolysis [73].…”
Section: Wnt/b-catenin; Dkk1 Frizzled Transmembrane Receptors and Sclerostinmentioning
confidence: 99%